Intimate partner violence and associated factors among reproductive age women in Liberia: a cross-sectional study using a recent Liberian demographic and health survey - Menen Tsegaw; Bezawit Mulat; Kegnie Shitu (BMC, 2022)
Abstract Background Intimate partner violence (IPV) is a major public health problem and a violation of women's human rights. Almost one third of women aged 15-49 years who have been in a relationship have experienced to some form of physical and/or sexual violence by their intimate partner worldwide. Objective The study aimed to assess the prevalence of intimate partner violence within the last 12 months and associated factors among reproductive aged women in Liberia. Method This study was based on a large community-based cross-sectional survey, Liberia Demographic Health Survey (LDHS), conducted From October 16, 2019, to February 12, 2020, in Liberia. The 2019-20 LDHS used a stratified two-stage cluster design. Multivariable logistic regression was used to identify independent intimate partner violence among reproductive age women in Liberia and to control confounders. Adjusted odds ratio and confidence interval (CI) were used to declare statistical significance in the final model. Those variables with p value < 0.05 were considered as statistically significant. Result The overall prevalence of IPV within the last 12 months was 44.74% (42.73-46.77). age of the women 41% (AOR = 0.59, 95%CI 0.37-0.93), 42% (AOR = 0.58, 95%CI 0.35-0.94), and 59% (AOR = 0.41, 95%CI 0.25-0.68) among women with in the age group of 35-39, 40-44 and 45-49 respectively, south central region (AOR = 0.71, 95%CI 0.52-0.96), women's primary education (AOR = 1.28, 95%CI 1.01-1.63), female household head (AOR = 0.77, 95%CI 0.61-0.97), husbands higher education (AOR = 0.62, 95%CI 0.39-0.99), positive wife beating attitude (AOR = 1.57, 95%CI 1.29-1.90), husband drinks (AOR = 2.59, 95%CI 2.14-3.15) and Women's decision making autonomy (AOR = 0.75, 95%CI 0.61-0.93) were significantly associated with IPV. Conclusion The prevalence of IPV in Liberia was high. Socio-demographic characteristics of women, husbands education, sex of household head, having a positive attitude towards wife-beating, partner's alcohol drinking habit and women empowerment was significantly associated with IPV in Liberia. Policymakers and program designers have to take into account those factors when they design interventions to reduce IPV in Liberia.